The effect of vertebral body stapling on spine biomechanics and structure using a bovine model. (April 2020) - Sunni, Nabeel; Askin, Geoffrey N.; Labrom, Robert D.; Izatt, Maree T.; Pearcy, Mark J.; Adam, Clayton J.
Abstract: Background: Adolescent idiopathic scoliosis is a common condition affecting 2.5% of the general population. Vertebral body stapling was introduced as a method of fusionless growth modulation for the correction of moderate idiopathic scoliosis (Cobb angles of 20–40°), and was claimed to be more effective than bracing and less invasive than fusion. The aim of this study was to assess the effect of vertebral body stapling on the stiffness of a thoracic motion segment unit under moment controlled load, and to assess the vertebral structural damage caused by the staples. Methods: Thoracic spine motion segments from 6 to 8 week old calves (n=14) were tested in flexion/extension, lateral bending, and axial rotation. The segments were tested un-instrumented, then a left anterolateral intervertebral Shape Memory Alloy (SMA) staple was inserted and the test was repeated. Data were collected from the tenth load cycle of each sequence and stiffness was calculated. The staples were carefully removed and the segments were studied with micro-computed tomography to assess physical damage to the bony structure. Visual assessment of the vertebral bone structure on micro-CT was performed. Findings: There was no change in motion segment stiffness in flexion/extension nor in axial rotation. There was a reduction in stiffness in lateral bending with 30% reduction bending away from the staple and 12% reduction bending towards the staple. Micro-CT showed physeal damage in all the specimens. Interpretation: Intervertebral stapling using SMA staples cause a reduction in spine stiffness in lateral bending. They also cause damage to the endplate epiphyses. Highlights: Current treatment for moderate scoliosis is limited. Vertebral body stapling is a less invasive method of treatment. Staple insertion resulted in a reduced stiffness in lateral bending only. Staple insertion causes physeal damage which may be responsible for correction.